Line positions and N2-induced line parameters of the 00°3–00°0 band of 14N216O by comb-assisted cavity ring-down spectroscopy. (May 2019) - Liu, G.-L.; Wang, J.; Tan, Y.; Kang, P.; Bi, Z.; Liu, A.-W.; Hu, S.-M.
Highlights: The spectrum of 00°3 – 00°0 band of 14 N2 16 O is studied with a laser-locked cavity ring-down spectrometer referenced to an optical frequency comb. 88 line positions are determined with an uncertainty below 1.0 MHz. N2 -induced broadening and shift coefficients of 20 isolated lines were retrieved with the voigt and quadratic speed-dependence voigt profiles. Comparisons of line parameters determined in this work with those given in literatures are discussed. Abstract: Ro-vibrational transitions of the 00°3–00°0 band around 1.52 µm with line intensities in the order of 10 −24 to 10 −23 cm −1 /(molecule·cm −2 ) have been recorded using a comb-assisted laser-locked cavity ring-down spectrometer with high sensitivity as well as high precision. In total, 88 line positions were determined with a sub-MHz uncertainty (1-σ), better than previous experimental results by 1–2 order of magnitude. N2 -induced line shape parameters of 20 isolated transitions were derived by using the Voigt profile and the quadratic Speed-Dependent Voigt profile with relative uncertainties of 1–2% (1-σ). Comparisons of the line parameters determined in this work with literature experimental values are given.